DINAMIKA DIGITALISASI DAN MANAJEMEN KEUANGAN UMKM: LITERATURE REVIEW IMPLEMENTASI FINTECH DAN DIGITAL MARKETING PADA UMKM - Affandi, Muhammad Rispan; Dasuha, Batista Leonardo P; Daniel Surya Parapat (Universitas Haji Sumatera Utara, 2025)
This study examines the dynamics of digitalization and financial management of Small and Medium Enterprises (SMEs) in Medan City, with a specific focus on the implementation of financial technology (fintech) and digital marketing. Through a systematic literature review approach, the research analyses scientific publications from 2019-2024 sourced from Google Scholar, Scopus, and Science Direct databases. The results show a positive trend in fintech adoption among SMEs in Medan, particularly in digital payment services and alternative financing, which has significantly impacted operational efficiency and access to financing. In terms of digital marketing, social media and e-commerce have emerged as key platforms effective in increasing market reach and sales. Although digital transformation still faces challenges such as limited infrastructure and digital literacy, the research identifies significant opportunities in market expansion and business innovation. The study concludes that the success of SMEs' digital transformation depends on effective technology integration and comprehensive digital ecosystem support, and recommends developing structured training programs and strengthening digital infrastructure to support SME digitalization in Medan City.